PENGARUH MODAL KERJA, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATU BARA TAHUN 2022-2024 - Wafiqoh, Qurratu A’yuni; Pramitasari, Triska Dewi; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The coal subsector within the mining industry represents a strategic sector that plays a vital role in energy provision and significantly contributes to the national economy. This study analyzes and examines the effects of working capital, profitability, and liquidity on firm value, with stock price as an intervening variable, in coal subsector mining companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This research adopts a quantitative method employing Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), utilizing Smart PLS 3.0 software. The sample comprises 12 companies selected through purposive sampling, resulting in 36 observational data points. Data were collected from the companies’ annual financial reports, which are available on the official IDX website. The findings reveal that working capital, profitability, and liquidity do not significantly affect stock price. Profitability has a positive and significant effect on firm value, whereas liquidity has a negative and significant effect on firm value. Working capital, stock price, and their indirect effects through stock price do not significantly affect firm value. Therefore, the stock price does not function effectively as a mediating variable in the relationship between the independent variables and firm value in the coal subsector.